Use of information and communication technologies to promote self-management of diabetic foot ulcers - Murillo Salamanca, Ana Maria; Alvarado-García, Alejandra María (Revista Cuidarte, 2022)
Introduction: Using information and communication technologies in nursing educational interventions facilitates self-management processes to adapt to chronic health conditions. Objetive:To evaluate the effect of a nursing educational intervention to promote self-management and prevent diabetic foot ulcers in Colombian adults with type 2 diabetes mellitus through information and communication technologies. Materials and Methods:A quasi-experimental, pre- and post-intervention study was conducted with 82 adults attending the chronic patient consultation of a second-level hospital in the department of Boyacá, Colombia. Participants were randomly allocated to the experimental and comparison groups. Results: There were no significant differences between the experimental and the comparison groups in terms of preintervention self-management scores. However, the experimental group’s mean self-management score was significantly higher than the control group’s six weeks after the intervention (p<0.005); the primary outcome was self-management behaviors from foot care. Nonparametric Wilcoxon and Mann Whitney tests were used. Discussion:Nursing interventions should be supported by theoretical approaches specific to the discipline, which allow visualizing specific results, in this case self-management, which requires strategies such as knowledge, skills and social support that will support adaptation to situations of chronic illness. Conclusions: The educational intervention based on the use of information and communication technologies improved self-management for preventing diabetic foot injuries, achieving a change in people’s behavior. How to cite this article: Murillo Salamanca Ana Maria, Alvarado García Alejandra María. Uso de tecnologías de información y comunicación para promover la autogestión de ulceras por pie diabético. Revista Cuidarte. 2022;13(2):e2254. http://dx.doi.org/10.15649/ cuidarte.2254